Psychometric properties of the Chilean version of the quality of life questionnaire for multiple myeloma - Luz Alejandra Lorca; Cinara Sacomori; Camila Peña; Claudia Barrera; Melissa Salazar; Ivana Leão; Ximena Valladares; Christine Rojas (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: To evaluate the internal consistency and construct validity of the QLQ-MY20 for assessing the quality of life in multiple myeloma survivors in Chile. Methods: This was a cross-sectional study conducted between March 2020 and December 2022. It involved 118 individuals from two public hospitals. The QLQ-C30 and QLQ-MY20 questionnaires were used. Internal consistency was assessed using Cronbach's alpha(α), and construct validity was evaluated through hypothesis testing (Mann-Whitney and Spearman correlation). Results: The average age of participants was 67.2 years (SD=9.2). Internal consistency for the complete scale was α=0.779, for the "disease symptoms" dimension α=0.671, for the "side effects of treatments" dimension α=0.538, and for the "future perspective" dimension α=0.670. Four of the five construct validity hypotheses were confirmed: women, individuals with worse performance status, those with pain, and those with worse fatigue showed more symptoms. Conclusions: The Chilean version of the QLQ-MY20 demonstrates adequate internal consistency and construct validity.